Rhyfeddod - Palacio, R. J.,Miles, Eiry (Rily Publications Limited, 2022)
Starting 5th grade at Beecher Prep, Auggie wants nothing more than to be treated as an ordinary kid - but his new classmates can't get past his extraordinary face. Wonder begins from Auggie's point of view, but soon switches to include the perspectives of his classmates, his sister, her boyfriend, and others.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books